2012
DOI: 10.1016/j.neuint.2012.02.028
|View full text |Cite
|
Sign up to set email alerts
|

The role of agrin in synaptic development, plasticity and signaling in the central nervous system

Abstract: Development of the neuromuscular junction (NMJ) requires secretion of specific isoforms of the proteoglycan agrin by motor neurons. Secreted agrin is widely expressed in the basal lamina of various tissues, whereas a transmembrane form is highly expressed in the brain. Expression in the brain is greatest during the period of synaptogenesis, but remains high in regions of the adult brain that show extensive synaptic plasticity. The well-established role of agrin in NMJ development and its presence in the brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 67 publications
3
36
0
Order By: Relevance
“…The effect of agrin on neuronal synapses is controversial. In peripheral ganglia, agrin participates in cholinergic synapse formation (38) but in the CNS its effects and effectors are unclear (39). We found that acute treatment with exogenous agrin was sufficient to induce a multiplicative scaling of inhibitory synapses that resembles activitydependent scaling up.…”
Section: Discussionmentioning
confidence: 85%
“…The effect of agrin on neuronal synapses is controversial. In peripheral ganglia, agrin participates in cholinergic synapse formation (38) but in the CNS its effects and effectors are unclear (39). We found that acute treatment with exogenous agrin was sufficient to induce a multiplicative scaling of inhibitory synapses that resembles activitydependent scaling up.…”
Section: Discussionmentioning
confidence: 85%
“…In Drosophila , the signal cannot be Agrin and in the mammalian CNS, Agrin is not essential for CNS synapse formation (Daniels, 2012). Thus, the Agrin-independence of CNS LRP4 may be conserved across systems.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated a substantial loss of excitatory synapses in the adult transgenic mice brain that lacked agrin expression. Further, they demonstrated inhibition of synaptogenesis by agrin antisense oligonucleotides or agrin siRNA in neuronal cell culture (reviewed in [88]). L1cam promotes the outgrowth of neurites and thereby contributes to formation of neuronal connections, learning, and memory [89], [90] via activation of the mitogen-activated protein kinase (MAPK) pathway [91].…”
Section: Discussionmentioning
confidence: 99%